Modern Slavery and Criminal Law: Literature on Legal Responses from Human Rights Perspectives - Kankana Das; Sharma, Prakash (University of Jember, 2025)
The complex issue of modern slavery affects millions. Notwithstanding global and local initiatives to eradicate it, it has manifested in various forms, including human trafficking, forced labour, debt bondage, and other forms of exploitation. This literature study aims to elucidate the pressing issue of contemporary slavery as a significant challenge, alongside an examination of the inadequacies present within the current legal framework in India. The primary inquiry revolves around the escalating threat of modern slavery in contemporary times. Here, the paper tries to examine, what are the current laws, and why are they ineffective in addressing the emerging forms of exploitation in the modern era? The scholarship on this topic originates from three overarching strands of writing. The first strand examines the detection of criminal exploitation and modern slavery within the current legal framework and advocates for the dedicated enforcement of these laws to protect vulnerable individuals from becoming victims of exploitation. The second research strand aims to analyse the economic markets and commercial entities in India to assess their compliance with regulations against modern-day slavery. Additionally, it seeks to enhance corporate responsibility by enforcing labour standards in supply chains. The third strand of literature focuses on the risk factors and root causes of contemporary slavery and criminal exploitation. In this perspective, the paper aims to understand, first, the exact processes through which modern slavery occurs; secondly, the factors that lead people to engage in exploitative situations, such as their already miserable and defenceless situation and their vulnerability to becoming victims of criminal activity; and thirdly, the possible preventive and corrective interventions. Keywords: Modern Slavery, Criminal Exploitation, Supply Chain, Business Entities, Human Rights.